LINGKUNGAN BISNIS DAN PERSAINGAN BISNIS RITEL - Tri Joko Utomo (STIE Pelita Nusantara Semarang, 2010)
The rapid development of retail business is driven by market opportunities, manufacturing business development, and government efforts to develop a retail business. This growth brings the impact of increasing competition in the retail business players. Retail business is divided into different types which vary based on classification according to shape, size, and level of modernity.Business environment consists of the internal environment in which the organization/ corporation has the ability to control it and the external environment that was divided into macro and micro external environment.Business competition can be analyzed using a systems approach to indicators known as the Structure-Conduct-Performance (SCP). Business competition descript from the market structure, strength, industry competition, and based on the level of product substitution.Retail competition can be viewed from various aspects, namely the competition between modern and traditional retail, competition among modern retailers, the competition among traditional retailers, and competition among suppliers